Higher prevalence of active asthma among 15-17 year-old Greek-Cypriots in socio-economically deprived communities in the vicinity of power plants: results of a nationwide survey In Cyprus - Middleton, Nicos; Kolokotroni, Ourania; Lamnisos, Demetris; Papathanassoglou, Elizabeth; Nicolaou, Christiana; Koutrakis, Petros; Yiallouros, Panayiotis Κ. (My University, 2014)
In contrast to the large body of literature on traffic pollution, there is only a handful of studies on the respiratory health of children in the vicinity of power plants, even though the energy industry is the main contributor to outdoor air pollution. METHODS: Based on responses to the ISAAC questionnaire of 5,817 15-17 year-old participants in a nationwide survey, we investigated: active asthma (i.e. report of asthma and wheeze and/or night time cough unrelated to colds in the past 12 months), inactive asthma and respiratory symptoms without a diagnosis in the vicinity of power plants in relation to the rest of the island. Associations in terms of GIS-calculated distance of the participants’ community to any of the three power plants were investigated in logistic models before and after adjusting for potential confounders. RESULTS: At 7.4% (95% CI: 4.5,11.3), the prevalence of active asthma at 5km from power plants appeared elevated compared to national levels, but any effect appeared restricted to the 5km-zone. Compared to >30 km away, those in the vicinity of power plants were nearly twice as likely to report active asthma with an adjusted OR of 1.83 95%CI (1.03, 3.24). No clear pattern was observed for inactive asthma while the OR of respiratory symptoms in the absence of diagnosis was 0.76 (95% CI: 0.58, 1.01), suggesting, if not diagnostic or reporting bias, an increased likelihood for symptomatic children to receive a diagnosis after more frequent or severe attacks. CONCLUSIONS: Higher prevalence of active asthma was observed in the vicinity of power plants, with no evidence of a distance-response relationship. Due to the small size of these communities, this corresponds to a small fraction of active asthma attributable to plant emissions but raises questions about environmental justice since the most affected communities are also socio-economically disadvantaged.
Keywords: Asthma; Children; Health